Web-Based Job Portal System with WhatsApp Integration for Interview Invitation and Verification Automation - Ade, Ade Agung Kurniawan; Suri, Riko Muhammad; Maharani , Putri Decelia (Universitas Medan Area, 2025)
In the digital era, job searches increasingly rely on online platforms that provide real-time job vacancy information. However, the conventional recruitment process still faces various obstacles, such as delays in information to applicants, the amount of administrative costs used by applicants in preparing documents to apply for jobs, vulnerable to fraudulent locker information from fake companies which of course this is detrimental and has an impact on job applicants. WhatsApp as the most popular communication media in Indonesia is a strategic opportunity in answering these challenges. This research aims to develop a digital-based job vacancy application with an integrated WhatsApp-based automatic verification interview invitation system and offer applicants the convenience of applying for a job and the ease of the Company in managing job applicant data to be more effective and efficient. This study is on the Instagram account @infokerjambi job vacancy media in Jambi Province with 50.1 thousand followers and 1.2 million profile impressions. Based on data from BPS Jambi Province, the Open Unemployment Rate (TPT) is 4.45. The Waterfaal model method used in this research and the test results show that the system is able to speed up the information process of sending interview invitations, reduce the potential for information delays because the system presents interview invitation features to wa applicants, applications and applicant emails in real time and increase security and trust in the recruitment process. For applicants, this system provides easy access to valid and real-time interview information, thus reducing the risk of fraud from verified companies. For companies, this system improves the management of applicant data management and administrative efficiency to reach a wider range of candidates.